A Criminological Review of Acts of Violence Committed by Children in Connection with Social Learning Theory - Naufal, Raden Hisyam Al; Guntara, Deny; Abas, Muhamad (Jurnal Hukum dan Keadilan, 2024)
Acts of violence committed by children, especially in the context of fights between students, are a serious issue that requires in-depth understanding. Recently, the harmony of national and religious life has been disturbed due to clashes that have brought about problems regarding children. Protection of children is the responsibility of parents, families and the surrounding community. The protection given to children is to guarantee and protect children and their rights to be able to live, grow, develop and also be able to socialize in the surrounding environment. The problem is how the criminological review of violent crimes committed by children is connected to social learning theory and how to formulate countermeasures for violent crimes committed by children in Karawang Regency. The research method used in this writing uses a normative juridical approach. The results of this research are that Social Learning Theory is very relevant in reviewing acts of violence from a criminological perspective where in cases that often occur in Karawang Regency, namely brawls between students, apart from that social learning theory can provide relevant insight in understanding brawls between students. that occur in Karawang Regency include 1) Observation and Imitation 2) Environmental Influence 3) Reinforcement and Punishment 4) The role of Schools and Teachers and efforts to overcome acts of violence committed by children in Karawang Regency, namely preventive efforts and repressive actions carried out by the police.